2010
DOI: 10.1007/s10554-010-9757-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced whole-heart coronary MRA at 3.0T for the evaluation of cardiac venous anatomy

Abstract: This study was designed to evaluate the value of contrast-enhanced whole-heart coronary MRA (CMRA) at 3.0T in depicting the cardiac venous anatomy. In cardiac resynchronization therapy (CRT), left ventricular (LV) pacing is achieved by positioning the LV lead in one of the tributaries of the coronary sinus (CS). Pre-implantation knowledge of the venous anatomy may help determine whether transvenous LV lead placement for CRT is feasible. Images of 51 subjects undergoing contrast-enhanced whole-heart CMRA at 3.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Whole-heart coronary MRA with additional slow infusion of contrast material (0.15 mmol/kg at 0.3 ml/sec) was acquired after perfusion imaging. A navigator-gated, electrocardiography-triggered, fat saturated, segmented 3D fast low-angle shot sequence [1,2], with the following image parameters was used: TR/TE/flip-angle = 3.0/1.4/20°, readout bandwidth = 610 Hz/pixel, voxel size = 1.3 × 1.3 × 1.3 mm 3 interpolated to 0.65 × 0.65 × 0.65 mm 3 , GRAPPA factor = 2, inversion prepulse delay = 200 ms. Delayed enhancement images were acquired by phase sensitive inversion recovery sequences after coronary MRA for viability study.…”
mentioning
confidence: 99%
“…Whole-heart coronary MRA with additional slow infusion of contrast material (0.15 mmol/kg at 0.3 ml/sec) was acquired after perfusion imaging. A navigator-gated, electrocardiography-triggered, fat saturated, segmented 3D fast low-angle shot sequence [1,2], with the following image parameters was used: TR/TE/flip-angle = 3.0/1.4/20°, readout bandwidth = 610 Hz/pixel, voxel size = 1.3 × 1.3 × 1.3 mm 3 interpolated to 0.65 × 0.65 × 0.65 mm 3 , GRAPPA factor = 2, inversion prepulse delay = 200 ms. Delayed enhancement images were acquired by phase sensitive inversion recovery sequences after coronary MRA for viability study.…”
mentioning
confidence: 99%
“…Lastly, these studies were done at 1.5T using a 6-channel coil. Studies have shown that image quality can be improved by performing studies on a 3T MRI with a 32 channel coil for maximum SNR [6]. However, most CMR studies are still performed at 1.5T because of better consistency of SSFP imaging at 1.5T [14].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using contrast-enhanced MRI for coronary vein imaging have shown that the technique is capable of visualizing the coronary venous vasculature [5, 6]. However, none of these studies have had corresponding X-ray venograms to validate the existence of the coronary veins visualized by MRI, and most studies have small sample sizes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial perfusion can be measured without CA by techniques of arterial spin labeling [71] and blood oxygen level-dependent contrast [15]. CA is used in myocardial angiography, where blood flow inside coronary arteries can be measured since the blood flow is alternated in the area of MI compared to the surrounding heart muscle [72]. CA-MRA has also been used to determine microvascular obstruction in swine acute MI model with high accuracy [22,71].…”
Section: Other Mri Techniquesmentioning
confidence: 99%